Peningkatan Pengetahuan dan Keterampilan Pembuatan Pakan Ikan Mandiri di Kelompok Pembudidaya Ikan Kecamatan Tamban Kabupaten Barito Kuala - Junius Akbar; Muhammad Adriani; Fatmawati (I-Com: Indonesian Community Journal, 2023)
In fish farming businesses, almost 60-70% of the total production costs are used to purchase feed. The aim of implementing this Community Service Activity (PKM) is to increase partners' knowledge and skills regarding techniques for making independent fish feed so that they can reduce the relatively expensive cost of feed. The method for implementing PKM activities is carried out in several stages, namely socialization and discussion in the form of counseling in the form of in-depth material and training in making independent fish feed. After the training activities are completed, assistance, monitoring and evaluation are carried out. The output of PKM activities is a product in the form of fish feed containing 22.96% protein; water 9.40%; fat 13.66%; ash 17.80% and fiber 8.42%. The fish feed produced has a price of Rp. 6,340/kg, cheaper compared to commercial fish feed of Rp. 11,500,-/kg. Thus, using independent feed for fish farming activities saves Rp. 5,160,- per kilogram.